MAKING WEBSITE THROUGH MEDIA CELL PHONE RESERVATION USING INTERNET PROGRAMS AND DATABASE MYSQL PHP - Yokiansyah Sasbriantoyo; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2007)
A complicated process but have a greater level of profit is not a priority anymore. In this day and age, more quickly process more attractive. The need for time held, requires that every person doing their activities efficiently.  Through various media, one of them is the internet media that can help meet all their needs for the process. Through a website, the information displayed in the form of more attractive and accessible from anywhere around the globe. Therefore the writer feels the need to meet information needs in the community by creating a website that provides information needed by Php and Mysql web programming to be more dynamic in the process information and understand the desires of the community.